Teaching Literature Through Film Adaptation The Case of 1st year Master Degree at the University of Djelfa - Boukhari ,Nacira; Nouioua ,Amira Hiba (Faculty of Letters and Foreign Languages Department of English, 2019)
Teaching English as a foreign language has been given much focus from the part of the scholars and the researchers of the field of English language teaching. Recently, English language teaching became challenging because of the changes of the variety of methods and techniques of teaching as well as the diversity of students’ interests, needs and motivations for learning. Therefore, teachers started to think about new ways to integrate new strategies to enhance the teaching process and make it more effective and result oriented. To this effect, the use of technology and multimedia became widely spread in so many domains including language teaching and teaching literature was no exception. The literature shows that he use of technology as well as film adaptation facilitates the learning and understanding of some of the most difficult literary works. Therefore, the present study was conducted to test the efficacy of adopting films in teaching EFL literature to first year Master degree students at the University of Ziani Achour in Djelfa, Algeria. To achieve the aim of the study two research instruments were utilized. These are a questionnaire to students and pre and post tests. The pre and post tests are part of the same instrument. The findings of the experimental study show that film adaptation is beneficial in the teaching of literature. The findings further support the argument which suggests that providing suitable learning atmosphere and increases the learners’ opportunities to understanding literary text as the results showed that most learners prefer to watch rather than to read. Also, learners who were interested in learning literature found that films facilitated comprehending some challenging themes of the Crucible. The current study results prove the effectiveness of films adaptation in literature courses as a technique of instructions. It has made the teaching of literature more exciting as it boosted students’ motivation and interest on learning the English literature. Hence, the study suggests that both teachers and learners should make use of film when teaching or learning literature